The Analysis of Factors That Influences People Intention to Use in Electronic Money - Fahiraningrum, Tasya Octaviani; Richard, Richard (LPPM Universitas Islam 45 Bekasi, 2020)
Abstract The development of banking service technology now allows us to do non-cash transactions using various media. Electronic money as one of the favorite media that is widely used by the public is now experiencing innovation with the new breakthrough of Electronic Money Flazz Gen 2 that can conduct transaction services via smartphones. With this latest innovation comes a question related to what factors that influence people using electronic money Flazz Gen 2. Therefore, quantitative research using a questionnaire conducted using the Technology Acceptance Model (TAM) analyzed using the Structural Equation Modeling – Partial Least Square (SEM-PLS) method assisted by software SmartPLS 3.0. The factors studied were taken from the variables in the Technology Acceptance Model (TAM) developed by Davis et.al (1996), namely perceived ease of use, perceived usefulness, and trust variables taken from Gefen's theory (2003). Keywords: TAM, Electronic Money, SEM-PLS,